Dilemma Between Applying Coherent Principle and Signaling Principles In Interactive Learning Media - Baharuddin, Baharuddin; Hadi, Sutarto; Abdul Hamid, Abdul Hamid; Abdul Mutalib, Ariffin; Dalle, Juhriyansyah (Bentham Open, 2018)
Background: Studies on developing multimedia content for eLearning have widely been conducted. In previous studies, multimedia learning contents were developed without applying any principles, making them less efficient in supporting user’s mental effort. To this end, this study extends the current state by applying the coherence principle and signaling principle to make the multimedia learning content usable and interesting to use. Furthermore, the paper aims at describing the dilemma when applying both principles together. Materials and Methods: In this study, a four-phase methodology has been used. First, a prototype has been developed by applying the coherence principle and signaling principle. Following the development, five experts were consulted for identifying flaws in the developed prototype through a walkthrough session. Results: Finally, this paper showcases the flaws gathered by the experts for further improvement.